PEMIKIRAN INKLUSIF ATAS DAMPAK PEMBANGUNAN TERHADAP KELESTARIAN SUMBERDAYA ARKEOLOGI - Tjahjono, Baskoro Daru (BRIN, 1996)
We always expect the ideal both in the implementation of development and in the management of archaeological resources. However, the reality on the ground is that these ideal expectations cannot always be fulfilled, on the contrary, the worst things happen. Development does not always have a positive impact, often development has a negative impact on efforts to conserve archaeological resources. .